2004
DOI: 10.1002/syn.20081
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of hippocampal cell proliferation in mice lacking the β2 subunit of the neuronal nicotinic acetylcholine receptor

Abstract: Adult hippocampal neurogenesis declines with age in parallel with decreased performance on a variety of hippocampal-dependent tasks. We measured the rate of cellular proliferation in the hippocampus of mice lacking the beta 2-subunit of the nicotinic acetylcholine receptor (beta 2-/- mice) at three ages: young adult (3 months old), fully adult (7-10 months old), and aged (22-24 months old). Consistent with previous studies, we observed an age-related decline in hippocampal proliferation in both groups. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 27 publications
2
42
1
Order By: Relevance
“…Conversely, systemic administration of the cholinergic agonist physostigmine increased dentate neurogenesis. The neurogenic effect of acetylcholine appears to involve nicotinic receptors containing the β2 subunit (Harrist et al, 2004), as well as m2, m3 and m4 muscarinic receptors (Ma et al, 2000;Mohapel et al, 2005). Consistent with these findings, ovariectomy upregulated m4 receptors in the dentate gyrus, whereas estrogen treatment restored m4 binding to the level of the sham group (El-Bakri et al, 2002).…”
Section: Subcortical Mediation Of Sex Steroid Effectssupporting
confidence: 63%
“…Conversely, systemic administration of the cholinergic agonist physostigmine increased dentate neurogenesis. The neurogenic effect of acetylcholine appears to involve nicotinic receptors containing the β2 subunit (Harrist et al, 2004), as well as m2, m3 and m4 muscarinic receptors (Ma et al, 2000;Mohapel et al, 2005). Consistent with these findings, ovariectomy upregulated m4 receptors in the dentate gyrus, whereas estrogen treatment restored m4 binding to the level of the sham group (El-Bakri et al, 2002).…”
Section: Subcortical Mediation Of Sex Steroid Effectssupporting
confidence: 63%
“…A combination of pharmacological and molecular genetic experiments has suggested that β2* nAChRs contribute to stress-induced behaviors and may contribute to the effects of antidepressant medications effective in human patients Harrist et al, 2004). The effect of α7 nAChRs on behaviors related to depression is more complex, however.…”
Section: Discussionmentioning
confidence: 99%
“…For example, injection into the lateral ventricle of IgG-saporin, which causes selective degeneration of cholinergic neurons, reduces DG neurogenesis with concurrent impairment of spatial memory in rodents (Cooper-Kuhn et al, 2004). The nAChRs also play a critical role to regulate neurogenesis based on a decline in hippocampal cell proliferation in mice lacking the nAChR ␤2 subunit (Harrist et al, 2004). In addition, restoration of neurogenesis in OBX was observed after chronic administration of citalopram, a serotonin-selective reuptake inhibitor (Jaako-Movits et al, 2006).…”
Section: Discussionmentioning
confidence: 99%